(3JZQjH GdYfOdjH Ydi YUf GdCfOdS GdQWjHs - (3CHh GdMLGL jhSa Hf eMeO Gdejdhi (B( (3Gdehdhi (B) (3GdeYQha HGHf Gdhcjds; (3GdebQjs
(3ChdgG (B:s
(3GdMeO ddg GdPi JaQO HGdOhGe hGdHbGA , hMce Ydi ef ShGg HGdRhGd hGdafGA hHYO , adeG CaQOfi GdOgQ Yf GdCNOGf , hCHYOfi Yf GdChWGf Edi Cf CfNJ GdeWjI HGdbGgQI GdeYRjI fbjH GdSGOI GdWGdHjjf s
(3BNQgG (B:s
(3bGd eNJUQg (B: (3gPG eG hbY Ydjg GdENJjGQ ef EbJWGa RgQ gPG GdZUf GdjGfY , hEfJTGb faN gPG GdWjH , hCOYh hYdi Gddg GdbHhd ade Bd LgOkG ai JgPjHg hGab GdaQGZ s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde ajg VHWs
(3fbdJ ef fSNI GdeDda HNWg GNJUQ Hg faM GdWjH ddebQis
(3hRGO Ydjg ahGFO s
(3hGfJgi efg ai TgQ Pi GdbYOI (B1114(3g` s
(3ai GdeYgO fSNI CNQi HQbe (B1512 (3JGQjN s
Keywords: (3GdJGQjNs